Incidence of COVID-19 among Vaccinated with Sputnik V and CoviVac Vaccines (Results of the Telephone Survey for the Epidemic Season 2021–2022 in St. Petersburg) - M. K. Erofeeva; O. V. Gashinskaya; Zh. V. Buzitskaya; T. G. Zubkova; E. V. Shakhlanskaya; M. A. Stukova; D. A. Lioznov (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. The emergence of a new SARS-COV-2 coronavirus in early 2020 radically changed the seasonal pattern of influenza and other acute respiratory infections worldwide. Along with a decrease in the frequency of RSV infection, the number of diagnosed cases of influenza virus infection decreased by 99% during the COVID-19 pandemic. Vaccines are known to be the best tool at our disposal for preventing infectious diseases and reducing the risk of serious complications and deaths. The Russian Federation has great experience in developing vaccines against viral and bacterial infections and is constantly improving the technology of their production putting new vaccine preparations into circulation. Domestic vaccines against a new coronavirus infection caused by SARS-CoV-2 virus were developed in the shortest possible time. This work evaluated the efficacy of Gam-Covid-Vac (Sputnik V) and CoviVac vaccines during periods of circulation of different variants of SARS-CoV-2 «Delta» and «Omicron» in St. Petersburg.Aims. To evaluate the prophylactic efficacy of domestic vaccines Gam-Covid-Vac (Sputnik V) and CoviVac in the epidemic season 2021–2022 in the periods of SARS-CoV-2 «Delta» and «Omicron» variants circulation in Saint-Petersburg.Materials and Methods. Vaccination and follow-up of vaccinated subjects was initiated in February 2021, with the arrival of the Gam-Covid-Vac (Sputnik V) and CoviVac vaccines at the specialized clinic of Smorodintsev Research Institute of Influenza. Follow-up of vaccinated subjects for one year after vaccination included 346 men and women aged 19-85 years, who were interviewed in two telephone surveys.Results. Telephone interviews among individuals vaccinated with Gam-Covid-Vaс (Sputnik V) and CoviVac vaccines revealed that during the circulation of «Delta» variant, 2nd half of 2021, COVID-19 disease occurred in 16.3% of people vaccinated with the CoviVac vaccine and in 15.8% of those vaccinated with Sputnik V vaccine – differences between groups were not statistically significant (p > 0.05). COVID-19 disease in both vaccine groups was predominantly mild with 61.95% of observed falling ill in the CoviVac vaccine group and 84.4% (slightly more, 1.4-fold) in Sputnik V vaccine group. At the same time, moderate and severe diseases were slightly more in absolute value among those vaccinated with "CoviVac" vaccine. Cough, lung damage from 30% to 80%, loss of sense of smell and taste dominated among the symptoms in both groups of patients. During the second observation period (January-April 2022), when «Omicron» variant were actively circulating, the number of cases among CoviVac and Sputnik V vaccines was 37.5% and 43.8%, respectively; the differences between the vaccine groups were not statistically significant (p > 0.05). During this period, diseases in CoviVac and Sputnik V vaccine groups were predominantly mild in 84.4% and 90.5%, respectively, with statistically insignificant differences. There were also no significant differences in cases of moderate severity. Among those observed in « CoviVac» group during this period, a greater number of diseases, in absolute value, proceeding in a severe form and requiring hospitalization was noted. Clinically, the diseases caused by «Omicron» variant manifested in symptoms characteristic of flu and common cold: headache and muscle pain, fever, chills, chest pain, nasal congestion, severe fatigue, fatigue, weakness.Conclusions. During periods of active « Delta» variant circulation in the fall of 2021patients vaccinated with SARS-COV-2 coronavirus vaccines were 2.3 to 2.8 times less ill than during circulation periods of «Omicron» variants ВА.1 и ВА.2 in January-April 2022: 16.3% and 15.8%, 37.5% and 43.8%, respectively. Mild COVID-19 disease predominated among patients vaccinated with both vaccines during periods of circulation of «Delta» and «Omicron» variants. Differences in the manifestation of clinical symptoms of the disease in the periods of circulation of different strains were noted. It was shown that the vaccines against SARS-CoV-2 infection Gam-Covid-Vac (Sputnik V) and CoviVac do not protect 100% against the disease, but protect against a severe course of the disease and lethal outcomes.